VD_FINDINFO HC / 2024 / 450 vom 7. Juni 2024 - VD Tribunal cantonal (2024)
ATTRIBUTION DE L'EFFET SUSPENSIF, EFFET SUSPENSIF, CLAUSE CONTRACTUELLE, PROHIBITION DE CONCURRENCE | 315 al. 4 let. b CPC (CH), 315 al. 5 CPC (CH)